Theoretical and Experimental Verification of Dynamic Behaviour of a Guided Spline Arbor Circular Saw - Ahmad Mohammadpanah; Stanley G. Hutton (Shock and Vibration)
An analysis of the dynamic and stability characteristics of a guided wood cutting spline arbor circular saw is presented. A multibody dynamic model is developed to consider the idling and cutting characteristics. The model considers the interaction between the blade, the arbor, and the guide pads. The model is capable of analyzing in-plane and out-of-plane edge forces which enables simulation of the cutting performance of the saw. In order to verify the computer model, an experimental test of a guided spline saw during idling run-up is presented. The frequencies and amplitudes of the blade vibrations are documented and plotted. Cutting tests are also conducted and the cutting forces are estimated. The results of a simulation of the idling response of the blade by the computer model and the experimental results are in a good agreement. Factors that significantly affect the characteristics of guided spline saws during cutting are discussed. The computer model is shown to be capable of predicting stable cutting operations of a guided spline saw.